2021
DOI: 10.3390/molecules26133876
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of Acidophilus-bifidus-thermophilus (ABT) Fermented Milk with Heat-Treated Industrial Yeast Enhances Its Selected Properties

Abstract: The improvement of milk dairy products’ quality and nutritional value during shelf-life storage is the ultimate goal of many studies worldwide. Therefore, in the present study, prospective beneficial effects of adding two different industrial yeasts, Kluyveromyces lactis and Saccharomyces cerevisiae pretreated by heating at 85 °C for 10 min to be inactivated, before fermentation on some properties of ABT fermented milk were evaluated. The results of this study showed that the addition of 3% and 5% (w/v) heat-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…There is scarce information on the use of Yo-mix 833 culture on fruit juices. Previous studies [27] have shown that fortification of yoghurt with chicken pea increased the viable cell count to 10 8 CFU/ml which agrees with our findings. Therefore, mango juice fermented with Fiti and Yo-mix culture maintained higher count levels than the minimum recommended values by Codex standards (10 6 CFU/ml) for a healthy probiotic product throughout the fermentation period.…”
Section: Cell Viability Of Abt-5 Fiti and Yo-mix Cultures During Ferm...supporting
confidence: 93%
See 1 more Smart Citation
“…There is scarce information on the use of Yo-mix 833 culture on fruit juices. Previous studies [27] have shown that fortification of yoghurt with chicken pea increased the viable cell count to 10 8 CFU/ml which agrees with our findings. Therefore, mango juice fermented with Fiti and Yo-mix culture maintained higher count levels than the minimum recommended values by Codex standards (10 6 CFU/ml) for a healthy probiotic product throughout the fermentation period.…”
Section: Cell Viability Of Abt-5 Fiti and Yo-mix Cultures During Ferm...supporting
confidence: 93%
“…The low cell count could be attributed to the pH of the fermented fruit juice being limiting factor for Abt-5 culture [13]. In addition, most of the beverages fermented with Abt-5 starter culture are milk based products with log 7.40 CFU/ml [27] and milk-fruit based formulations with 3.7×10 9 CFU/ml [29] which gives higher viable count than the current study. Researchers reported lower counts in bifidobacteria in preparation of functional probiotic dairy beverages fortified with pomegranate juice [30].…”
Section: Cell Viability Of Abt-5 Fiti and Yo-mix Cultures During Ferm...mentioning
confidence: 78%
“…Recently, lased-treated Lb. casei had higher free radical scavenging activity than nontreated cells [66,67].…”
Section: Impact Of Probiotication Of Dairy Foods On Enhancement Of Th...mentioning
confidence: 83%
“…Antioxidant potential was evaluated by ferric reducing antioxidant power (FRAP), 2,2 -Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and 2,2-diphenyl-1-picrylhydrazyl-hydrate (DPPH) according to [21,26]. Powdered L. sativum sprouts were extracted by aqueous ethanol (80%, v/v) and centrifuged for 20 min at 14,000× g. Subsequently, antioxidant activity assessment was performed by combining 0.1 mL diluted sprout extracts with 0.25 mL of the DPPH, ABTS or FRAP reagents.…”
Section: Antioxidant Activitymentioning
confidence: 99%